Введення у культуру Marrubium vulgare L. у Лівобережному Лісостепу України - Derkach, V.O.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The features of ontogenesis, productive potential and adaptive possibilities of the introduced species of white horehound Marrubium vulgare L. have been investigated. Possibilities of cultivating plants under the conditions of the Left-Bank of Forest-Steppe of Ukraine are demonstrated. The productivity of raw material (air-dry grass) and seeds in the first year and following years are investigated. The contents of the pharmacological active substances in the Marrubium vulgare are determinate.